Social-Ecological Systems and Human Well-Being - Zorondo-Rodriguez, F (Springer International Publishing, 2019)
Human well-being is a socio-cultural construct, originated within human experiences, that changes through time. The current literature shows a renewed interest to develop new measures and approaches to relate it to the progress of nations. One of the challenges is whether inequality is a key component and how to measure it. Furthermore, are indicators appropriate for the realities and diversity of environments of Latin American countries? In this chapter, we analyze human well-being and its subjective and objective dimensions in social-ecological systems. We propose that one way to study the relationships between both concepts is through an ecosystem services perspective. This includes the social-ecological interactions reflecting human-nature dependencies and their contributions to the well-being of local people and local and national economies. Its application shows a direct dependence of subsistence economies within Latin American rural zones on those services. One consequence is that these zones will be more affected by the degradation of ecosystems than populations from developed countries. Latin American countries still have important groups of ancestral populations whose social, cultural, and economic development has occurred within society-nature interactions for hundreds of years, shaping their well-being. We assert that their co-evolution and adaptations to maintain their interactions are of worldwide interest since they represent learning experiences for contemporary cultures that may help on the generation of co-learning and management structures. © Springer Nature Switzerland AG 2019. All rights reserved.